Merancang Manajemen SDM Berbasis Kompetensi - Sudarmanto Sudarmanto (Magister Administrasi Publik, 2005)
Public servants human resource management, as the main driving force for the conduct of state task, recently has been viewed rigid, formalistic, unadaptive and late in anticipating global change. The national employee system is unable yet to push the rise of strong apparatus, competency, clean, responsible and professional. The performance accountability system of employee is neither clear yet. DP3—usually used as judgement for evaluating employee performance is unable yet to reflect the real profile of employee performance. Reward and punishment system can not also reflect justice and certainty yet, so that it is unable yet to motivate employee work more maximal. To be able to overcome such, it is necessary to develop the apparatus management system based competency. An alternative of approach based on behavior is determinant factor for superior performance. The concept of competency consists : motives, traits, self concept, knowledge and skill.